Konstruksi Teks Pada Media Kompas dalam Pemberitaan Kasus Setyanovanto - Sri Rahayu (Resolusi: Jurnal Sosial Politik, 2018)
The news about e-KTP corruption has attracted public attention thaks to the role of media that continually publish the case. This paper tries to explain the news of alleged corruption cases involving Setyanovanto, especially in Kompas media, using framing analysis. By analising several articles in Kompas media, this study concludes that news framing can construct public perception. The inappropriate process of framing the news on detailed content descriptions can further confuse the public. Thus according to the framing analysis, which is derived from the theory of social construction, the reality of news has not fulfilled the three aspects namely aspect of social, aspects of construction, aspects of reality.